The serotonergic system and the control of breathing during development - Cummings, Kevin J. (Respir Physiol Neurobiol, 2019)
Serotonin (5-HT) was first discovered in the late 1940’s as an endogenous bioactive amine capable of inducing vasoconstriction, and in the mid-1950’s was found in the brain. It was in these early years that some of the first demonstrations were made regarding a role of brain 5-HT in neurological function and behavior, including some of the first data implicating reduced brain levels of 5-HT in clinical depression. Since that time, advances in molecular biology and physiological approaches in basic science research has intensely focused on 5-HT in the brain, and the many facets of its role during embryonic development, post-natal maturation, and neural function in adulthood continues to be established. This review focuses on what is known about the developmental roles for the 5-HT system, which we define as the neurons producing 5-HT along with pre-and post-synaptic receptors, in a vital homeostatic motor behavior - the control of breathing. We will cover what is known about the embryonic origins and fate specification of 5-HT neurons, and how the 5-HT system influences pre- and post-natal maturation of the ventilatory control system. In addition, we will focus on the role of the 5-HT system in specific respiratory behaviors during fetal, neonatal and postnatal development, and the relevance of dysfunction in this system in respiratory-related human pathologies including Sudden Infant Death Syndrome (SIDS).